Photography Booking and Management System for Karya Kita using Laravel Frameworks - Ali, Aida Madihah; Mohd Zin, Nur Ariffin (Applied Information Technology And Computer Science, 2026)
This paper presents the development of a Photography Booking and Management System for Studio by Karya Kita, aimed at addressing operational inefficiencies such as double bookings, missed appointments, and poor payment handling caused by manual processes. The system automates the booking process, integrates payments, and generates QR-based receipts to streamline the operations of the studio. Developed using an object-oriented approach, the frontend of the system was created using Android (with Dart/Flutter), while the backend was powered by Laravel, a PHP framework, facilitating easy management of database interactions. The project employed the Prototyping methodology to allow iterative development based on user feedback. The system is validated through alpha and beta testing to ensure its functionality and user satisfaction. Key findings from user acceptance testing revealed a significant reduction in scheduling conflicts, enhanced operational transparency, and improved client satisfaction. User feedback showed high satisfaction across all areas, with ratings ranging from 88% to 96%. The QR Code feature was the highest-rated at 96%, followed by Ease of Login and Overall Satisfaction at 94%. Other key features like Booking Experience, Admin Calendar, and Payment Upload also scored above 90%, indicating strong system performance and a positive user experience.The solution ensures scalability and continuous service availability, particularly during high-demand events such as convocations, allowing the studio to manage increased bookings without issues. Future recommendations for system improvement include integrating mobile applications for real-time bookings and expanding the payment solution for better scalability during peak periods.